Water supply and sewerage disposal for housing in Canlubang-new town - Nwaji, Chibuike Sam-hannah 1945- (1978)
The dynamism at which our contemporary society grows, makes great demand on the field of utility design in planning for housing. Several decades of study, guide and control of this development have matured to become an essential and integral element of our methodology in resolving urban problems. Canlubang is growing from small agricultural community, which hardly make big demands on water supply and sewerage disposal system; into a more fragmented and more sophisticated community with more urban characteristics. Compared to other factors that have contributed to the standard of living in our modern civilization, it would appear that water supply and sewage disposal systems have grown and attracted public notice very slowly. The average citizen does not therefore seem to be aware of the tremendous amount of work involved; or the large expenditure made to provide adequate and satisfactory water supply and sewage disposal systems. Water is a primary requisite for the maintenance of all life. The amount of water needed by a single individual is small though. But when individuals band together to form communities, villages, towns and cities; the water requirement multiply man-folds. Water is the life-blood of a community. Its value in our everyday life, in fact its necessity in making life possible in any community, can only be suggested by considering what would happen if the public water supply were to be suddenly and completely turned off. The consequence will obviously be veritable chaos. Water therefore becomes one of the primary requisites for the growth of a community. Rivers and other sources or bodies of water form the principal sources of the greater part of the water supply for thickly populated areas. On the other hand, almost all the water supplied becomes sewage. Proper disposal of the quantity of sewage, as is expected in the study areas at full development, is extremely important from the point of view of health and general well-being of the community. For small population spread over relatively large areas, natural methods may be adequate. Danger from disease increases with population growth and congestion. Most often domestic sewage and other wastes are frequently discharged into those sources of water supply. This usually creates critical environmental situation, when a community has assumed a certain stage of growth. At times, not until this stage is reached would the community and the planners realize that the problem of utilities for housing has become a matter of public, rather than an individual concern. The roots of planning these two systems lay in the measures to avert dirt, squalor and disease for an urban survival of the industrial man. It was basically out of concern for these that some standards are worked out, adapted, and accepted for the planning of these systems, among others. It is but a normal expectation for the need for a better control over sources of nuisances to arise.
Vita.
Thesis (Master of Architecture)--University of the Philippines, Diliman
Keywords: Sewerage -- Canlubang (Laguna).; Sewerage -- Environmental aspects -- Canlubang (Laguna).